PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN METODE EKSPERIMEN UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN PEMAHAMAN KONSEP PADA MATERI ELEKTROLISIS SISWA SMA NEGERI 3 JAYAPURA - Martono, Anton Djoko; Siregar, Tiurlina (Jurnal Ilmu Pendidikan Indonesia, 2013)
This study aims to: (1) to improve the students critical thinking skills, (2) to improve the students understanding of the concepts, (3) to know the differences of critical thingking skills between students who experience learning with PBL through experimental methods with conventional methods, (4) to know the differences of understanding of concepts between students who experience learning with PBL through experimental method with conventional method. The research method used is a quantitative method using a quasi-experimental study involving 40 subjects of SMA Negeri 3 Jayapura XI class science school year 2012/2013. Population consisted of 87 students, and samples were taken using cluster random sampling technique. The data used in this study is the data of studentâs pretest and posttest. Results of data analysis showed that the PBL models with experiments can be: 1) improve studentâs critical thinking skills (n-Gain experiment class = 0.74 and 0.48 n-Gain control class), 2) improve the understanding of the concept of students (n-Gain experiment class = 0.76 and 0.53 n-Gain controll class), 3) there are differences in critical thinking skills among students taught throught experiments with PBL models with conventional methods (sig < 0.05 or sig = 0.000), 4) there is a difference understanding concepts among students taught through experiments with PBL models with conventional methods (sig < 0.05 or sig = 0.001), 5) improve attitudes to find and solving problem, and 6) their positive attitude. Keyword : problem based learning (PBL) , experiment method, critical thinking skills, understanding of concepts.